Using poly(N-Vinylcaprolactam) to Improve the Enzymatic Hydrolysis Efficiency of Phenylsulfonic Acid-Pretreated Bamboo - Lv, Xianqing; Yang, Guangxu; Gong, Zhenggang; Cheng, Xin; Shuai, Li; Huang, Liulian; Chen, Lihui; Luo, Xiaolin; Liu, Jing (Frontiers in Bioengineering and Biotechnology, 2021)
Chemical pretreatment followed by enzymatic hydrolysis has been regarded as a viable way to produce fermentable sugars. Phenylsulfonic acid (PSA) pretreatment could efficiently fractionate the non-cellulosic components (hemicelluloses and lignin) from bamboo and result in increased cellulose accessibility that was 10 times that of untreated bamboo. However, deposited lignin could trigger non-productive adsorption to enzymes, which therefore significantly decreased the enzymatic hydrolysis efficiency of PSA-pretreated bamboo substrates. Herein, poly(N-vinylcaprolactam) (PNVCL), a non-ionic surfactant, was developed as a novel additive for overcoming the non-productive adsorption of lignin during enzymatic hydrolysis. PNVCL was found to be not only more effective than those of commonly used lignosulfonate and polyvinyl alcohol for overcoming the negative effect of lignin, but also comparable to the robust Tween 20 and bovine serum albumin additives. A PNVCL loading at 1.2 g/L during enzymatic hydrolysis of PSA pretreated bamboo substrate could achieve an 80% cellulosic enzymatic conversion and meanwhile reduce the cellulase loading by 3 times as compared to that without additive. Mechanistic investigations indicated that PNVCL could block lignin residues through hydrophobic interactions and the resultant PNVCL coating resisted the adsorption of cellulase via electrostatic repulsion and/or hydration. This practical method can improve the lignocellulosic enzymatic hydrolysis efficiency and thereby increase the productivity and profitability of biorefinery.